Effects of non-protein-type amino acids of fine particulate matter on E-cadherin and inflammatory responses in mice. Issue 3 (17th September 2015) - Chuang, Hsiao-Chi; Ho, Kin-Fai; Cao, Jun-Ji; Chuang, Kai-Jen; Ho, Steven Sai Hang; Feng, Po-Hao; Tian, Linwei; Lee, Chii-Hong; Han, Yong-Ming; Lee, Chun-Nin; Cheng, Tsun-Jen
Highlights PM2.5 was collected from Beijing, Xian and Hong Kong during haze episodes. OC, EC and free amino acids of PM2.5 were characterised. BALB/c mice were received an aspiration exposure of PM2.5. PM2.5 caused pulmonary inflammation and E-cadherin inhibition. Non-protein type amino acids were associated with inflammation.